Gene profile in BRCA-negative breast cancer with the family history: a case report - Kołacińska, Agnieszka; Kusińska, Renata; Wasylecka-Morawiec, Maja; Morawiec, Zbigniew (Menopause Review/Przegląd Menopauzalny, 2012)
Hereditary breast cancer accounts for 4-10% of all cases; the majority of them are caused by BRCA1 and BRCA2 mutations. We report a case of a 29-year-old breast cancer patient, BRCA -negative, with the following family history: her mother was diagnosed with breast cancer at the age of 40 and her sister – with ovarian cancer at the age of 40. Her breast cancer tissue sample submitted was analyzed by MammaPrint, a 70-gene profile of breast cancer for the metastatic risk. The gene profile result showed high risk, which means that a lymph node-negative breast cancer patient has a 29% chance (95% CI 22-35) that her cancer will recur within 10 years without any adjuvant treatment.